Catalytic assemble of 2-amino-5, 6-dimethyl-1H-benzimidazole with carboxylic acids and evaluation of their antimicrobial and antioxidant activities. Issue 5 (October 2016) - M., Aruna Sindhe; Bodke, Yadav D.; R., Kenchappa; Telkar, Sandeep; A., Chandrashekar; B.M., Vinoda
الملخص: أهداف البحث: تم تحضير سلسلة من الكاربوكسيميدات المستبدلة ب Nـ (٦٬٥- ثنائي ميثيل-١H -بنزيميدازول-٢-yl) بتفاعل ٢- أمينو- ٦٬٥-ثنائي ميثيل- ١H - بنزيميدازول مع أنواع متعددة من الأحماض الكاربوكسيليكية العطرية الحلقية غير المتجانسة والنشطة بيولوجيا، ومع أنواع من الأحماض الدهنية باستخدام عوامل مساعدة عدة. طرق البحث: تم التأكد من بنية المركبات المستحضرة بواسطة الرنين المغناطيسي النووي من نوع ١ H و ١٣ C، والطرق الطيفية الجماعية. كما فُحصت المركبات المُعَنوَنَة لتحديد نشاطها المضاد للميكروبات و المضاد للأكسدة. النتائج: أظهرت المركبات " ٣هـ " و "٣و" و " ٣ز" و " ٣ح" و " ٣ي" و " ٣ ل" نشاطا مشجعا ضد الميكروبات التي تم اختبارها وذلك بقيم تركيزات مثبطة دنيا تتراوح بين ٢٥٠ إلى ٧٥٠ ميكروغرام/مل. وأظهرت المركبات " ٣ز" و " ٣ح" و " ٣ي" قدرة واضحة على التخلص من الجذور ونشاطا مخلبيا ضد الحديدوز بقِيَم تثبيطية من ٤٩٬٠٠± ٦٥ إلى ٥٧٬١٨ ± ٨٩ ميكروغرام/مل. الاستنتاجات: أظهرت جميع المركبات المستحضرة أنشطة مضادة للميكروبات ومضادة للأكسدة جيدة. كما كشفت هذه الدراسة أن إضافة حلقة غير متجانسة أو إضاقة سلسلة مفتوحة مقابِلة في الموضع الثاني من حلقة البنزِيميدازول يُنتج مركبات ذات فاعلية حيوية أكثر. Abstract: Objectives: A series of N-(5, 6-dimethyl-1H-benzimidazol-2-yl) substituted carboxamide was synthesized using the reaction of 2-amino-5, 6-dimethyl-1H-benzimidazolewithvarious bioactive aromatic heterocyclic carboxylic acids and fatty acids with several catalysts. Methods: The structures of the synthesized compounds were confirmed using 1 H and 13 C nuclear magnetic resonance (NMR) and mass spectroscopic methods. The title compounds were screened for antimicrobial and antioxidant activity. Results: Compounds 3e, 3f, 3g, 3h, 3j and 3l exhibit promising antimicrobial activity against the tested microorganisms with minimal inhibitory concentration (MIC) values of 250–750 μg/ml. Compounds 3g, 3h and 3j show prominent radical scavenging and ferrous ion chelating activity, with IC50 values of 49.00 ± 65 to 57.18 ± 89 μg/ml. Conclusion: All of the synthesized compounds show good antimicrobial and antioxidant activities. This study reveals that the incorporation of a heterocyclic ring and open-chain counterparts at the second position of the benzimidazole ring yields more potent biologically active compounds.